2020
DOI: 10.1101/2020.08.25.20182022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in back pain scores after bariatric surgery in obese patients: A systematic review and meta-analysis

Abstract: Objective: To evaluate if back pain scores in morbidly obese patients change after bariatric surgery. Summary Background Data: Obese patients often complain of low back pain (LBP), however the underlying mechanism is not fully understood. Recent research shows that, next to mechanical loading, the chronic low-grade inflammation that arises in obese patients is contributing to LBP due to intervertebral disc degeneration. Therefore, it is hypothesized that bariatric surgery will have an effect on the LBP in obes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(100 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have indicated that excess adipose tissue in the body can lead to chronic low-grade inflammation, resulting in pain and increased disability (Hussain et al, 2017;Kawai et al, 2021;Zheng et al, 2022). However, some research has shown that a decrease in BMI may not be associated with the severity of back pain and disability after bariatric surgery or physiotherapy treatment (Mangwani et al, 2010;Koremans et al, 2021), which is consistent with our study. Pain is the subjective experience.…”
Section: Severity Of Pain and Disabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have indicated that excess adipose tissue in the body can lead to chronic low-grade inflammation, resulting in pain and increased disability (Hussain et al, 2017;Kawai et al, 2021;Zheng et al, 2022). However, some research has shown that a decrease in BMI may not be associated with the severity of back pain and disability after bariatric surgery or physiotherapy treatment (Mangwani et al, 2010;Koremans et al, 2021), which is consistent with our study. Pain is the subjective experience.…”
Section: Severity Of Pain and Disabilitysupporting
confidence: 92%
“…Overweight is associated with many common health conditions, such as joint degeneration, increased pain, and poor daily activity performance (Pataky et al, 2014;Chen et al, 2021;Goode et al, 2022). Previous studies have reported that overweight is one of the main contributing factors of DLD (Hussain et al, 2017;Parenteau et al, 2021).…”
Section: Introductionmentioning
confidence: 99%